Best Answer

Without an equality sign the given terms can't be considered to be any kind of an equation whatsoever..

Q: Is (2x - 5) 2 0 a quadratic equation or not?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

3x2-2x-2 = (3x-3.645751311)(x+0.5485837704) when factored with the help of the quadratic equation formula

4x2 - 4x + 1 = 0 => (2x - 1)(2x - 1) = 0 => (2x - 1)2 = 0 There is one solution: x = 1/2. It is a repeated root of the equation.

Start with a quadratic equation in the form � � 2 � � � = 0 ax 2 +bx+c=0, where � a, � b, and � c are constants, and � a is not equal to zero ( � ≠ 0 a =0).

You know an equation is quadratic by looking at the degree of the highest power in the equation. If it is 2, then it is quadratic. so any equation or polynomial of the form: ax2 +bx+c=0 where a is NOT 0 and a, b and c are known as the quadratic coefficients is a quadratic equation.

It is a quadratic equation and its solutions are: x = -3/2 and x = 3

Related questions

No. It is a quartic equation. The largest power of x in a quadratic equation must be 2.

there is no problem with this quadratic equation it's 2x square - 3x -2 = 0 I need an answer. where it says square there should be a little 2 at the top corner of the 2x to make it 2x square thanks If you can't factor it easily then use the quadratic equation: The two solutions are: 2 & -.5

3x2-2x-2 = (3x-3.645751311)(x+0.5485837704) when factored with the help of the quadratic equation formula

4x2 - 4x + 1 = 0 => (2x - 1)(2x - 1) = 0 => (2x - 1)2 = 0 There is one solution: x = 1/2. It is a repeated root of the equation.

To solve for x in the equation x2 - 2x - 2 = 0, use the quadratic equation, that is: For 0 = ax2 + bx + c, the roots (values of x) are defined as: x = [-b +/- sqrt(b2 - 4ac) ] / 2a (If that's hard to understand, google "quadratic formula"). It works out to x = 2.73, -0.73.

x2 + 2x + 2 = 0 Use the quadratic formula: x = (-2 +- sqrt(4 - 8))/2 x = (-2 +- 2i)/2 = -1 +- i

Divide all terms by -2: 4x2+4x+1 = 0 (2x+1)(2x+1) = 0 x = -1/2 and also x = -1/2 The quadratic equation has 2 equal roots.

x*2+4x+8= 0 is a quadratic equation

It is a quadratic equation and its solutions are: x = -3/2 and x = 3

x2 - 2x - 5 = 0 By the quadratic equation, x = {2 +/- sqrt[(-2)2 - 4*1*(-5)]}/2 = {2 +/- sqrt(4+20)}/2 =1 +/- sqrt(6)

Start with a quadratic equation in the form � � 2 � � � = 0 ax 2 +bx+c=0, where � a, � b, and � c are constants, and � a is not equal to zero ( � ≠ 0 a =0).

x = 7/2 and also x = -3/2 by using the quadratic equation formula.